DEVELOPMENT AND MODELING OF THREE PHASE INVERTER FOR HARMONIC IMPROVEMENT USING SINUSOIDAL PULSE WIDTH MODULATION (SPWM) CONTROL TECHNIQUE - EVENNA, LINGKING (UNIVERSITI MALAYSIA SARAWAK(UNIMAS), 2018)
The final year project report with a title of Development and Modeling of Three Phase Inverter for Harmonic Improvement Using Sinusoidal Pulse Width Modulation (SPWM) Control Technique is presented. The inverter converts electrical signal from Direct Current (DC) to Alternating Current (AC). An internal control technique of an inverter is Pulse Width Modulation (PWM) technique. The Sinusoidal Pulse Width Modulation (SPWM) technique is a type of the PWM that is used in this project to control the output of the inverter. Today, harmonics has become the common problem because there are many modern electronics equipment. The incidence of harmonic related problems in power system distribution is high, so awareness of harmonic issue can help to increase plant power reliability. The objectives of the final year project are to model and simulate the three phase inverter system with a suitable topology using the MATLAB Simulink software, to develop a control strategy of the three phase inverter circuit, to design and demonstrate the laboratory prototype for three phase inverter and last but not least to analyze the total harmonic distortion (THD) for the three-phase inverter using the proposal SPWM control. The development and modeling of three phase inverter for harmonic improvement by using the SPWM control technique is implemented in the software and hardware parameters. The software that is used in the project is MATLAB Simulink. The hardware that are used in the project are Digital Signal Processors (DSPs), Printed Circuit Board (PCB), Gate Driver Circuit and Insulated Gate Bipolar Transistor (IGBTs) switches. A perfect sine wave and smooth supply are obtained from the inverter using the SPWM technique. The minimum of harmonic incidence are obtained from the project outcomes. Hence, the SPWM technique improved the performance of equipment and the power quality.